Influence of Fluoride Ions Contamination in Front Opening Unified Pod (FOUP) Generating Defective Bonding Pad - Kwon, Soon Seok; Hwang, Sung Min; Kim, Hyoung Ryeun; Jang, Hee Chang; Hong, Jeong Hoon; Song, Gil Joo; Park, hyun Yul; Kim, Minsoo; Shin, Youhwan; Kim, Jin Young; Noh, Tae Yong; Yoo, Seoung-Kyo (TAIWAN ASSOC AEROSOL RES-TAAR, 2017)
We analyzed defective bonding pad in various ways and determined the causes of defects that boosts oxidation of aluminium by fluoride residue on surface of pad with moisture. Additionally, we compared and evaluated methods to minimize pad defects in aspects such as etching and wafer storage environment. In case of wafers after pad open etching process using common CF4 stored in FOUP, the concentration of fluoride ions in FOUP was 230 ng L-1 and it decreased down to 170 ng L-1 when Ar sputtering step was added after using CF4. Also under the same condition, fluoride ion concentration in FOUP decreased down to 20 ng L-1 when nitrogen purge was introduced for 10 minutes to the FOUP where wafers were stored and the moisture also decreased from 40% before purge to 10% after purge. As a result of observation on pad surface after storing wafers in FOUP for 120 hours under each condition, negligible amount of defects were found when nitrogen was purged. Therefore, we conclude that defects on pad were generated by existing fluoride ions after etching process and moisture in the air.
Keywords: 300 MM WAFER; AIRBORNE MOLECULAR CONTAMINATION; COPPER WIRE; CORROSION; NITROGEN